(untitled) (Texas Journal of Medical Science, 2022)
Modern biology, especially the sciences of physiology and biophysics, is characterized by the importance of studying the mechanisms of transport processes from cell membranes as well as the calcium homeostasis of cells. Because calcium ions play an important role in many cellular processes, including cell excitability, muscle contraction and relaxation, mediators and hormone secretion, and a number of other physiological processes. Therefore, as a result of disruption of calcium homeostasis in cells, the functional activity of cells is impaired. This can lead to certain pathological conditions in the body and the development of various diseases.